Knowledge of Tour Guides in the Sekumpul Waterfall Regarding Occupational Health and Safety - Made Adhyatma Prawira Natha Kusuma; Ni Luh Gede Aris Maytadewi; Luh Putu Wulandari Artha; Rut Wiratami (Universitas Negeri Malang, 2024)
Occupational health and safety is an important thing to pay attention to in any activity, one of which is in the tourism sector. In the world of tourism, many tourism activities are offered by tourism business actors, which must pay attention to the health and safety of the tourism offered. The purpose of this study was to see the level of knowledge, attitudes, and behavior of tour guides at the Sekumpul Waterfall tour, Buleleng Regency, Bali regarding occupational health and safety. This research is a cross-sectional study using a descriptive-analytic approach with a one-group pretest-posttest research design. The sampling technique used accidental sampling. The number of samples in this study was 76 people. Data were analyzed descriptively quantitatively using the Paired Samples T Test and presented in the form of a frequency distribution table, then compared descriptively. The results showed that the level of knowledge in the good category of respondents before receiving education was 57.89 percent. Then after receiving education the level of knowledge of the respondents in the good category increased to 72.37 percent. Based on the Paired Samples T Test results, the value of p is 0.001 was obtained, which means education effectively increases respondents' knowledge regarding K3 in tour guides at Sekumpul Waterfall tour. Suggestions that can be recommended in this study are that the Sekumpul Waterfall tour manager needs to pay attention to the preparedness of the tour guide in carrying out his work. It is necessary to carry out periodic guidance related to Occupational Health and Safety and disaster preparedness.